Nanoscale 3D spatial analysis of FTO/ZnO/Ag-x films subjected to photocatalytic activity - Leila Chehreghani Anzabi; Azizollah Shafiekhani; Elham Darabi; Mirosław Bramowicz; Sławomir Kulesza; Jamshid Sabbaghzadeh; Shahram Solaymani (Scientific Reports)
Abstract The study focuses on FTO/ZnO/Ag-x films (with different silver dopant levels) fabricated using the sol–gel/spin-coating technique. The optical, structural, and geometrical properties of these films were characterized through various methods, such as Photoluminescence (PL) spectroscopy, UV–visible spectroscopy, X-ray diffraction (XRD), and Field Emission Scanning Electron Microscopy (FESEM). Key findings include a reduction in transmittance and an increase in absorbance in the visible spectrum due to the interaction between silver and ZnO, enhancing photocatalytic properties. The optical band gap decreased from 3.23 to 2.80 eV with higher silver doping, suggesting the presence of Localized Surface Plasmon Resonance (LSPR). Structural analysis confirmed a hexagonal wurtzite phase for ZnO and a body-centered cubic phase for silver, with polycrystalline layers forming on a single-crystalline FTO substrate. The films show potential for photocatalytic applications, particularly in water-splitting hydrogen production, and their photoelectrochemical performance as photoanodes was quantified.